Global photographies : memory - history - archives - Michels, Stefanie, 1971-; Helff, Sissy (Image (Transcript (Firm)) ;, 2018)
"How is photography connected to global practices? This is a first edited collection to trace the relationship between history, photography and memory in a global perspective on three interrelated levels: firstly, in the artistic and cultural production of pictures, secondly, in the decoding of colonial and contemporary photography, and thirdly, in collecting photographs in picture archives dealing with colonial and anthropological photography. The contributions sketch the contested field of (post- )colonial photography and trace the manifold intertwinements between historical and contemporary photographs"--Back cover.